The Effect of Fuel Prices on Food Prices in Kenya - Ngare, Lucy W.; Derek, Okova W. (International Journal of Energy Economics and Policy, 2021)
High food prices are one of the major risks facing households from developing countries. Food prices have attracted renewed interest among policy experts in identifying appropriate policy instruments to counter the effect of price vulnerability. This paper evaluates the effect of fuel prices on food prices by testing for Granger causality and cointegration applied to diesel, maize, beans, cabbage, and potatoes price data for the period 2010-2018. The results revealed a unidirectional Granger causality running from diesel prices to cabbage and potatoes prices but there was no causal relationship with maize and beans prices. The findings suggest that there is a long-run price relationship between perishable foods and fuel prices with an increase in the price of diesel resulting in a significant increase in the price of cabbages and potatoes. The study recommends a policy of cushioning an increase in food prices by introducing a tax relief once the fuel price hits a certain level. Keywords: Food prices, Fuel prices, Cointegration, Granger causality JEL Classifications: Q48, Q43, Q13 DOI: https://doi.org/10.32479/ijeep.10600